Association Between Medications Acting on the Central Nervous System and Fall-Related Injuries in Community-Dwelling Older Adults: A New User Cohort Study. (22nd November 2019) - Gray, Shelly L; Marcum, Zachary A; Dublin, Sascha; Walker, Rod; Golchin, Negar; Rosenberg, Dori E; Bowles, Erin J; Crane, Paul; Larson, Eric B
Abstract: Background: It is well established that individual medications that affect the central nervous system (CNS) increase falls risk in older adults. However, less is known about risks associated with taking multiple CNS-active medications. Methods: Employing a new user design, we used data from the Adult Changes in Thought study, a prospective cohort of community-dwelling people aged 65 and older without dementia. We created a time-varying composite measure of CNS-active medication exposure from electronic pharmacy fill data and categorized into mutually exclusive categories: current (within prior 30 days), recent (31–90 days), past (91–365 days), or nonuse (no exposure in prior year). We calculated standardized daily dose and identified new initiation. Cox proportional hazards models examined the associations between exposures and the outcome of fall-related injury identified from health plan electronic databases. Results: Two thousand five hundred ninety-five people had 624 fall-related injuries over 15, 531 person-years of follow-up. Relative to nonuse, fall-related injury risk was significantly greater for current use of CNS-active medication (hazard ratio [HR] = 1.95; 95% CI = 1.57–2.42), but not for recent or past use. Among current users, increased risk was noted with all doses. Risk was increased for new initiation compared with no current use (HR = 2.81; 95% CI = 2.09–3.78). Post hoc analyses revealed that risk was especially elevated with new initiation of opioids. Conclusions: We found that current use, especially new initiation, of CNS-active medications was associated with fall-related injury in community-dwelling older adults. Increased risk was noted with all dose categories. Risk was particularly increased with new initiation of opioids.